1990
DOI: 10.1159/000461112
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Blood Component Collector: Plasma Separation Using Gravity without any Electrical Devices

Abstract: A new type of blood component collector (BCC) was developed to divide 450 ml of whole blood into plasma and a red cell concentrate using gravity without electrical devices. This BCC system is composed of one whole blood collection bag, two product collection bags and a plasma separator, which consists of a bundle of hydrophilized polyethylene hollow fibers (0.2 pm pore size). Without rinsing the plasma separator, the whole blood (458.1±13.5 ml, n = 22) was run through the separator using gravity without a pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, acceptable FVIII (69–79% of initial activity present after 1 year of storage) activity has been demonstrated for human FFP as required by the Council of Europe (16) despite a decline in plasma protein content and coagulation factor activity due to postulated absorption by the HF system (12). The utilization of polyethylene instead of polyethersulfone fibers in the filter system showed no obvious impairment of coagulation factor activity in a previous study (34). However, none of the previous studies performed a direct comparison between the two separation methods as we did.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, acceptable FVIII (69–79% of initial activity present after 1 year of storage) activity has been demonstrated for human FFP as required by the Council of Europe (16) despite a decline in plasma protein content and coagulation factor activity due to postulated absorption by the HF system (12). The utilization of polyethylene instead of polyethersulfone fibers in the filter system showed no obvious impairment of coagulation factor activity in a previous study (34). However, none of the previous studies performed a direct comparison between the two separation methods as we did.…”
Section: Discussionmentioning
confidence: 59%
“…In previous studies, separation times of 40 and 44 min were described using a not further specified Fresenius and a Pall leukodepletion filter (12, 14) similar to the filter used in this study. Studies not using any leukodepletion filter reported a separation time of 11 and 15 min although they used a HF system with similar fiber diameter (328 μm) as in our study but smaller pore size (0.2 μm) andlower wall thickness (30 μm) (11, 34).…”
Section: Discussionmentioning
confidence: 67%
“…First attempts with integrated special plasma filters to separate the whole blood into its components were carried out at the beginning of the 1990s. The major problems with these filter systems (BBC, Asahi, Tokyo, Japan) were the long separation time and the insufficient concentration ability of the filter systems 26‐28 …”
Section: Discussionmentioning
confidence: 99%
“…The major problems with these filter systems (BBC, Asahi, Tokyo, Japan) were the long separation time and the insufficient concentration ability of the filter systems. [26][27][28] With a newly developed special hollow-fiber filtration system (Sangofer, Heim Group), Hornsey and colleagues 1 showed that it is possible to process RBCs of adequate quality without any other equipment. In this study, we were able to show that by use of a modification of the above-mentioned system (Sangofer neonatal, Heim Group), it is also possible to separate placental blood into its compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques require important facilities and heavy investments (specific infrastructures, expensive equipment, welltrained staff, and well-controlled procedures) [8,9]. New separations' technologies using closed-system gravity filtration with hollow-fibers system has also been developed [9][10][11]. In Sub-Saharan African lowincome countries, either centrifugation/aphaeresis methods or gravity filtration system are all often out of reach.…”
Section: Introductionmentioning
confidence: 99%